(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
“Education is not only the right, but the duty of every Muslim, male or female. The best gift from a father to his child is education and upbringing. Knowledge cannot be acquired with sloth.” Education is the key factor for any kind of human development, prosperity and welfare of any society. As we are all aware, education is necessary for optimal growth. It is especially true for women, who make up a weaker and more marginalized segment of society. We have a significant gap in our knowledge and comprehension of Muslim culture from an experienced point of view since there are so few social science research studies on Muslims in India, specifically Muslim women from West Bengal. Because they were not exposed to contemporary schooling, Muslim women sometimes engage in cultural and social events more than do women of other religions. The current study makes an effort to analyse the educational challenges faced by Muslim girls enrolled in Paschim Medinipur’s secondary and upper secondary schools in West Bengal. The descriptive survey approach was used as the investigational strategy for the current research. The sample for the current research included 150 Muslim females from 10 upper secondary schools in the Paschim Medinipur District, 60 of who were dropouts, including 75 rural, 75 urban, and 30 rural and 30 urban Muslim girls. The researcher created her own questionnaire to learn about the issues facing the sampled females. The survey found no discernible difference between Muslim females from rural and urban areas in terms of issues with securing scholarships and dropping out of higher education. However, the investigator discovered a considerable disparity in the occurrence of discrimination andharassment of Muslim females in upper secondary school in rural and urban areas.